2023
DOI: 10.23876/j.krcp.22.111
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamon: an aromatic condiment applicable to chronic kidney disease

Abstract: Cinnamon, a member of the Lauraceae family, has been widely used as a spice and traditional herbal medicine for centuries and hasshown beneficial effects in cardiovascular disease, obesity, and diabetes. However, its effectiveness as a therapeutic intervention forchronic kidney disease (CKD) remains unproven. The bioactive compounds within cinnamon, such as cinnamaldehyde, cinnamicacid, and cinnamate, can mitigate oxidative stress, inflammation, hyperglycemia, gut dysbiosis, and dyslipidemia, which are commonc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 174 publications
(200 reference statements)
0
5
0
Order By: Relevance
“…For example, the use of turmeric was positively associated with participants who had heart disease while ginger intake was positively associated with participants who had cancer. Even though human clinical trials are limited with different spices, those that have focused on certain pungent spices such as garlic, ginger, turmeric, black pepper have shown improvements in health conditions [ 19 , 21 , 23 , 30 32 ]. As demonstrated in reviews, turmeric leads to reduction in inflammation, blood pressure, oxidative stress and others due to its active compound curcumin [ 33 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the use of turmeric was positively associated with participants who had heart disease while ginger intake was positively associated with participants who had cancer. Even though human clinical trials are limited with different spices, those that have focused on certain pungent spices such as garlic, ginger, turmeric, black pepper have shown improvements in health conditions [ 19 , 21 , 23 , 30 32 ]. As demonstrated in reviews, turmeric leads to reduction in inflammation, blood pressure, oxidative stress and others due to its active compound curcumin [ 33 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Spices and herbs have been used for medicinal purposes for centuries in various cultures [19,20]. Studies have shown that inflammation can be reduced, which improves renal and cardiac functions, if the individual consumes spices and herbs such as clove, garlic, ginger, turmeric, rosemary, and pepper due to the active components that are able to inhibit inflammatory pathways [19][20][21][22][23]. Currently, the amount and frequency of spice and herb intake among the CKD population is not known, nor if their dietary intake as quantified by diet quality has an association with spice and herb consumption.…”
Section: Introductionmentioning
confidence: 99%
“…This effect is also facilitated by stimulating liver kinase B1‐mediated AMPK phosphorylation. Moreover, the cinnamon extract has been associated with inhibiting α‐glucosidase and pancreatic α‐amylase activities, which ameliorate postprandial glycemic levels [63].…”
Section: Nutritional Strategies To Mitigate the Inflammationmentioning
confidence: 99%
“…To date, no studies in patients with CKD elucidated the beneficial effects of cinnamon. However, a recent literature review explored the promising effects of cinnamon on various conditions found in patients with CKD [63]. Thus, common pathways support the salutogenic effects of cinnamon in CKD, including mitigation of inflammation through inactivation of the p38 MAPK pathway, along with stimulation of the Nrf2 pathway, promoting a decrease in kidney damage with consequent preservation of its function [63].…”
Section: Nutritional Strategies To Mitigate the Inflammationmentioning
confidence: 99%
“…Cinnamon compounds such as cinnamaldehyde, trans-cinnamaldehyde, cinnamic acid and cinnamyl acetate also may improve the gut barrier integrity and modulate the gut microbiota, promoting the growth of salutogenic bacteria [ 121 ]. Beetroot is known to alter the oral bacteria species, transforming NO 3− to NO 2− increasing nitric oxide (NO) synthesis.…”
Section: Gut Microbiota Modulation and Effects On Residual Kidney Fun...mentioning
confidence: 99%